1977
DOI: 10.1021/ja00461a031
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of linear octene cations in the gas phase

Abstract: hypochromism (i.e., association) in two pyrimidine-C3-pyrimidine series, upon increasing alkyl group size, but decreased quantum yields of dimerization. (a) Replacing the 5-methyl group in T-Qj-T by ethyl: K. Golankiewicz and L. Strekowski, Mol. Photochem., 4,189 (1972). (b) Increasing the size of the 3-alkyl group in bis-3-alkylated T-C3-T derivatives: K. Golankiewicz and A. Zasada-Parzynska, Bull. Acad. Pol. Scl., 22, 945 (1974).(35) The triplet 1,4 diradical which precedes dimer closes three times less e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 2 publications
2
20
0
Order By: Relevance
“…molecular ions, and their [C,H,]+ daughter thus been identified among molecular ions of C,H8 ions are presented in Table 1. together with the (3, C5Hlo (lo), C,H,, ( l l ) , C6H12 (lo), C7Hl, (2), kinetic energy releases evaluated from the halfand C8Hl, (9). From the above it is evident that the height widths of the metastable peaks for CHIe loss.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…molecular ions, and their [C,H,]+ daughter thus been identified among molecular ions of C,H8 ions are presented in Table 1. together with the (3, C5Hlo (lo), C,H,, ( l l ) , C6H12 (lo), C7Hl, (2), kinetic energy releases evaluated from the halfand C8Hl, (9). From the above it is evident that the height widths of the metastable peaks for CHIe loss.…”
Section: Introductionmentioning
confidence: 88%
“…Incomplete atom randomization prior to fragmentation on the ps time scale only becomes prevalent in ions containing six or more C atoms, e.g., in dimethylpentenes (9, heptenes (6,7), C,H,, isomers (8), and octenes (9).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of the isomeric octenes (16), it was concluded that the molecular ions had isomerised isotopic labelling ( 6 ) , have led to the identification of to a common structure (or structures) in less than reacting configurations of fragmenting ions, daughter s. However, at times shorter than 10-1° s, the ion structures, and, in some cases, where good decomposing molecular ions retained their structural thermochemical data are available, to the identifica-integrity and decomposed by specific mechanisms. tion of the neutral fragment's structure as well (7).…”
Section: Introductionmentioning
confidence: 99%
“…' This and corresponding statements6 which are in conflict with our conclusion reached from collisional activation spectra of isomeric octanes that alkane molecular ions retain their original structure prior to decomp~sition,~ prompted us to review the original t Author to whom correspondence should be addressed $For Part VII, see Ref. 32. Ltd, 1911 mass spectrometric literature on labelled n-alkanes and to carry out this additional study on I3C and 2H labelled n-dodecane.…”
Section: Introductionmentioning
confidence: 97%